Enemies and allies : an unforgettable journey inside the fast-moving & immensely turbulent modern Middle East - Rosenberg, Joel C., 1967- (Tyndale House Publishers, 2021)
Do recent changes in the Middle East signal peace? One Arab country after another is signing historic, game-changing peace, trade, investment, and tourism deals with Israel. At the same time, Russia, Iran, and Turkey are forming a highly dangerous alliance that could threaten the Western powers. Meanwhile, the U.S. is drawing down its military forces in the Mideast and focusing on matters closer to home. Where's it all heading?